2021
DOI: 10.1063/5.0060367
|View full text |Cite
|
Sign up to set email alerts
|

What the foundations of quantum computer science teach us about chemistry

Abstract: With the rapid development of quantum technology, one of the leading applications that has been identified is the simulation of chemistry. Interestingly, even before full scale quantum computers are available, quantum computer science has exhibited a remarkable string of results that directly impact what is possible in a chemical simulation with any computer. Some of these results even impact our understanding of chemistry in the real world. In this Perspective, we take the position that direct chemical simula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 92 publications
0
4
0
Order By: Relevance
“…We test known quantum techniques and others that we introduce, covering all key aspects of quantum simulation: state preparation, Hamiltonian simulation, and the extraction of physical observables. Thus, we characterize the resources needed to realize a “digital experiment” of quantum molecular dynamics ( 18 ) on early fault-tolerant quantum computers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We test known quantum techniques and others that we introduce, covering all key aspects of quantum simulation: state preparation, Hamiltonian simulation, and the extraction of physical observables. Thus, we characterize the resources needed to realize a “digital experiment” of quantum molecular dynamics ( 18 ) on early fault-tolerant quantum computers.…”
Section: Discussionmentioning
confidence: 99%
“…This approach involves representing wave functions over a grid of points; thus, the method explicitly encodes features such as particle symmetry (unlike the conventional second-quantized formulation). We select this approach as it is appealingly intuitive, but moreover, first-quantized simulation is anticipated by many researchers to offer the optimal resource scaling for complex and interesting molecules ( 9 , 11 , 18 ); some have even suggested that first-quantized simulation can efficiently encode both nuclear and electronic degrees of freedom on an equal footing, potentially addressing the gap in simulating non–Born-Oppenheimer processes in modern chemical physics ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…The VQE scales badly for large molecules (due to repeated measurements/tomography to form the expectation value of the Hamiltonian, Ĥ . Nevertheless, the VQE is the common approach for small molecules with present NISQ QPUs [115][116][117][118]. The phase-estimation algorithm (PEA) scales better, but involves much deeper circuits, puts much higher demands on the coherence time of the q-register, and needs advanced QEC.…”
Section: Vqe Basicsmentioning
confidence: 99%
“…For an overview of applications to chemistry, see reviews [116][117][118] and specific applications [45,72,73,114,[119][120][121][122][123][124][125][126][127][128][129][130][131].…”
Section: Vqe Applied To Chemistrymentioning
confidence: 99%